If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(x+5)=6x+4(x-2)
We move all terms to the left:
-2(x+5)-(6x+4(x-2))=0
We multiply parentheses
-2x-(6x+4(x-2))-10=0
We calculate terms in parentheses: -(6x+4(x-2)), so:We get rid of parentheses
6x+4(x-2)
We multiply parentheses
6x+4x-8
We add all the numbers together, and all the variables
10x-8
Back to the equation:
-(10x-8)
-2x-10x+8-10=0
We add all the numbers together, and all the variables
-12x-2=0
We move all terms containing x to the left, all other terms to the right
-12x=2
x=2/-12
x=-1/6
| k+19/6=6 | | 4(1/4+c)=1.25 | | 3.1=1.3-0.5y | | 2q^2–98=0 | | 4x+3×(36-×)=124 | | u/6-16=5 | | 263-w=183 | | 8x^2-8=528 | | 169=76-x | | f-72/7=3 | | 2x+7=5x-4-x | | 4(1/4+c)=1/1/4 | | 260=-w+169 | | 2j-2=22 | | 4(1/4+c)=11/4 | | −4(−1.2x+1)=2.9(x-10)+2.4x | | (78-24)/3=c | | (7x-21)=(-5x+75) | | 6.5+a=-2.5 | | 17-2m=1 | | 55=x/13 | | 38000-600m=18800 | | 1=2u-13 | | 3(1.4-6)-8X=-2+5(2x+1) | | 5=9q+2q^2 | | 36x+24+56=12x+24 | | n+6n+2n=9n | | 46=5x^2 | | 2+2v=4v | | 9x+16=-12 | | -2c+5=-1 | | x=5x2+20x+16 |